An Analysis of Critical Thinking Skills and Communication in Science Education : A Study of Grade VIII Students - Fani, Salvi Dwi; Indrawati, Indrawati; Astutik, Sri (Universitas Pendidikan Mandalika, 2025)
This study aims to analyze the level of students' critical thinking and communication skills in science learning, identifying areas of strength and weakness. A descriptive quantitative method was employed, with tests and questionnaires as instruments. This research involved 73 students from the eighth grade of a junior high school as respondents. The data analysis technique used in this research is quantitative descriptive analysis. The results of this study indicate that the level of critical thinking and communication skills of junior high school students has a significant gap in science learning. In this study for critical thinking skills, each indicator is providing simple explanations (65%) in the medium category, building basic skills (51%) in the low category, concluding (45%) in the low category, providing advanced explanations (41%) in the low category, and organizing strategies and tactics (28%) in the very low category. And for communication skills, each indicator is Expressing 45% (low), Evaluating 42% (low), Responding 59% (medium), Negotiating 49% (low). Students' critical thinking and communication skills are in the low category, this indicates the need to improve learning strategies that encourage active involvement and reflective thinking of students.